GALERI SENI LUKIS BANJARBARU - Rahmah, Annisa; Muchamad, Bani Noor (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
Art galleries have a role as a means for artists to exhibit their work and a means for the public to enjoy and obtain information about art on a non-formal basis. Galleries cannot be passive institutions that only provide space for art collections, but must also provide space for the public to